Left atrial and ventricular malignant cardiac tumour in a 62-year-old woman: a case report - Banyś, Andrzej; Wągrowska-Danilewicz, Małgorzata; Kordek, Radzisław; Kasprzak, Jarosław; Peruga, Zbigniew; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Sarcoma is one of the most common malignant primary heart tumours. It accounts for over 76-95% of malignant heart tumours. It can cause serious complications such as pulmonary and peripheral embolism, reduced atrial and ventricular filling, and subsequently reduced cardiac output, arrhythmias, valve dysfunction, and sudden cardiac death. For these reasons early diagnosis and subsequent surgical treatment are the most important. However, complete resection of sarcomas is not always possible and the long-term prospects for resected malignant tumours are adverse. In this article we present a case report of the surgical excision of a left atrial and ventricular sarcoma in a 62-year-old woman.